Characterization of end-of-life LEDs: Mapping critical, valuable and hazardous elements in different devices. (September 2022) - Vinhal, Jonathan Tenório; de Oliveira, Rafael Piumatti; Coleti, Jorge Luis; Espinosa, Denise Crocce Romano
Highlights: The heterogeneity of LED waste requires specific methods of characterization. Greater concentrations of critical and rare earth metals are found in WW LEDs. As and Pb are seen in LED models, even with toxic metal restriction laws in EEE; Unlike CW and RED, Ga was seen as an aluminate phosphor in WW. With a greater density of phosphor particles, WW LEDs emit yellowish light. Abstract: LEDs are essential components in the vast majority of technologies. Over the years, to maintain the comfort of modern life, an increase in the generation of LED waste has been observed. It is known that LED wastes are potential sources for recovering critical, valuable, and rare earth metals. Therefore, this study aims to provide a complete characterization of LED models: cold white (CW), warm white (WW), and RED, mapping potential elements to be recovered and hazardous elements to the environment and public health. The LED models were analyzed by ICP-OES, SEM-EDS, and FTIR-ATR. It was observed in WW a higher concentration of Ce, Ga, and Y than in CW and RED due to its greater density of phosphor particles in the encapsulant material. In, Ga, Ag, and Au were seen in LED dies of WITHES, while As, and Ga were identified in RED LED dies. Pb was observed in the solder of CW and RED. LEDs' encapsulant and polymeric structures are polydimethylsiloxane (PDMS) and polyamide 11, respectively. The study findings showed a wide variation in metal contents and distribution regarding different LED models. Those variations were pointed out, providing opportunities for developing future works aimed at recycling and treating LED waste.